Cingulate and thalamic metabolites in obsessive-compulsive disorder. (30th August 2016) - O'Neill, Joseph; Lai, Tsz M.; Sheen, Courtney; Salgari, Giulia C.; Ly, Ronald; Armstrong, Casey; Chang, Susanna; Levitt, Jennifer G.; Salamon, Noriko; Alger, Jeffry R.; Feusner, Jamie D.
Abstract: Focal brain metabolic effects detected by proton magnetic resonance spectroscopy (MRS) in obsessive-compulsive disorder (OCD) represent prospective indices of clinical status and guides to treatment design. Sampling bilateral pregenual anterior cingulate cortex (pACC), anterior middle cingulate cortex (aMCC), and thalamus in 40 adult patients and 16 healthy controls, we examined relationships of the neurometabolites glutamate+glutamine (Glx), creatine+phosphocreatine (Cr), and choline-compounds (Cho) with OCD diagnosis and multiple symptom types. The latter included OC core symptoms (Yale-Brown Obsessive-Compulsive Scale – YBOCS), depressive symptoms (Montgomery-Åsberg Depression Rating Scale – MADRS), and general functioning (Global Assessment Scale – GAS). pACC Glx was 9.7% higher in patients than controls. Within patients, Cr and Cho correlated negatively with YBOCS and MADRS, while Cr correlated positively with the GAS. In aMCC, Cr and Cho correlated negatively with MADRS, while Cr in thalamus correlated positively with GAS. These findings present moderate support for glutamatergic and cingulocentric perspectives on OCD. Based on our prior metabolic model of OCD, we offer one possible interpretation of these group and correlational effects as consequences of a corticothalamic state of elevated glutamatergic receptor activity alongside below-normal glutamatergic transporter activity. Highlights: MRS glutamate+glutamine in pregenual anterior cingulate is elevated in adult OCD. MRS choline- and creatine compounds in cingulate and thalamus vary with severity of symptoms. Results give some evidence for OCD as a glutamatergic, cingulocentric, and ADHD-like disorder. Our model of OCD explains the co-occurrence of glutamatergic, choline and creatine effects.